2018
DOI: 10.1039/c7ra12289f
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of simple, low cost and benign sol–gel Cu2InxZn1−xSnS4alloy thin films: influence of different rapid thermal annealing conditions and their photovoltaic solar cells

Abstract: Cu2InxZn1−xSnS4 (x = 0.4) alloy thin films were synthesized on soda lime glass (SLG) substrate by a simple low-cost sol–gel method followed by a rapid annealing technique.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
(53 reference statements)
1
5
0
Order By: Relevance
“…As shown in Figure 2a, strong diffraction peaks at 2θ = 28.53, 32.99, 47.33 and 56.17° were observed for all films, which were assigned to the (112), (200), (220) and (312) diffraction planes of kesterite CZTS (JCPDS card no. 26-0575) [26,27]. In addition, two weak peaks were observed at 2θ = 69.27° and 76.44°, which were ascribed to the (008) and (332) planes of kesterite CZTS [28], suggesting that the crystalline quality of the Cu 2 Mg x Zn 1− x SnS 4 films was satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 2a, strong diffraction peaks at 2θ = 28.53, 32.99, 47.33 and 56.17° were observed for all films, which were assigned to the (112), (200), (220) and (312) diffraction planes of kesterite CZTS (JCPDS card no. 26-0575) [26,27]. In addition, two weak peaks were observed at 2θ = 69.27° and 76.44°, which were ascribed to the (008) and (332) planes of kesterite CZTS [28], suggesting that the crystalline quality of the Cu 2 Mg x Zn 1− x SnS 4 films was satisfactory.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, CZTSSe is considered to be a potential absorber material. However, the conversion efficiency of CZTSSe photovoltaic cells hasonly achieved 12.6%, which is still far lower than the conversion efficiency of CIGSe-based solar cells (22.9%) [7,8,9]. In order to improve conversion efficiency and make CZTSSe industrially viable, a lot of researches are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Various research groups have conducted extensive research to study the impact of In doping on the CZTSSe absorber thin films . Some research groups have reported the substitution of Zn sites by In, as Zn 2+ (0.74 Å) has a comparable ionic radius to In 3+ (0.80 Å). , Furthermore, the peak for the corresponding (112) plane shows a decrease in the relative peak intensity for higher (In-CZTSSe-3) and lower (In-CZTSSe-3) In-doped samples. It could be observed due to the inadequate In doping amount in CZTSSe samples, which may deteriorate the absorber quality.…”
Section: Resultsmentioning
confidence: 99%